RHO-3 plays a significant role in hyphal extension rate, conidiation, and the integrity of the Spitzenkörper in Neurospora crassa - Ornelas Llamas, Martha; Pérez Mozqueda, Luis Leobardo; Callejas Negrete, Olga; Castro Longoria, Ernestina (My University, 2024)
The Rho family of monomeric GTPases act as signaling proteins to establish and maintain cell polarity and other essential cellular processes. Rho3 is a GTPase of the Rho family that is exclusive of fungi that regulate cell polarity in yeast. However, studies have yet to explore its function in filamentous fungi. In this work, we investigated the role of RHO-3 in the model organism Neurospora crassa. Confocal microscopy analysis revealed that RHO-3 localizes in the outer region of the Spitzenkörper (Spk), in the plasma membrane from region II to the beginning of region III, and in the septa of mature hyphae. The phenotypic effect of the rho-3 deletion was analyzed. The results revealed that the rho-3 null strain showed severe defects in growth rate, aerial hyphae length, and conidia production. The organization of the Spk is also affected in the absence of RHO-3. Co-expression analysis of GFP-RHO-3 with glucan synthase 1 (GS-1-mChFP) and chitin synthase 1 (CHS-1-mChFP) revealed that RHO-3 localizes in the external region of the Spk in the macrovesicles zone. In summary, our results suggest that RHO-3 is not essential for the polarized growth of hyphae but plays a significant role in hyphal extension rate, conidiation, sexual reproduction and the integrity of the Spk, possibly regulating the delivery of macrovesicles to the apical dome.
PublMed
Keywords: Macrovesicles; N. crassa; RHO-3; Rho-GTPase; Spitzenkörper.; Campus Ensenada